Atmospheric reductive catalytic fractionation of lignocellulose integrated with one-pot catalytic conversion of carbohydrate yielding valuable lignin monomers and platform chemicals from corn straw - Meng-Ying Liu; Zhe-Hui Zhang; Xue-Qi Wang; Qian Sun; Chen Zhang; Yu Li; Zhuohua Sun; Katalin Barta; Feng Peng; Tong-Qi Yuan (Green Energy & Environment)
Developing a cost-effective and environmentally friendly process for the production of valuable chemicals from abundant herbal biomass receives great attentions in recent years. Herein, taking advantage of the “lignin first” strategy, corn straw is converted to valuable chemicals including lignin monomers, furfural and 5-methoxymethylfurfural via a two steps process. The key of this research lies in the development of a green and low-cost catalytic process utilizing magnetic Raney Ni catalyst and high boiling point ethylene glycol. The utilization of neat ethylene glycol as the sole slovent under atmospheric conditions obviates the need for additional additives, thereby facilitating the entire process to be conducted in glass flasks and rendering it highly convenient for scaling up. In the initial step, depolymerization of corn straw lignin resulted in a monomer yield of 18.1 wt%. Subsequently, in a dimethyl carbonate system, the carbohydrate component underwent complete conversion in a one-pot process, yielding furfural and 5-methoxymethylfurfural as the primary products with an impressive yield of 47.7%.